THE EFFICACY OF THE COOPERATIVE LEARNING TECHNIQUE IN ENHANCING FUNDAMENTAL BASKETBALL ABILITIES AMONG MIDDLE SCHOOL PUPILS - Alsaedi, M. Mazin Abdulaaima Kadhim (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2025)
This study will be conducted to test the effectiveness of cooperative learning methods in improving the basic basketball skills of fifth-grade preparatory students in a preparatory school in Maysan Governorate. The study design was an experimental one that used two-group design, experimental and control group, which contained pre-test and post-test results. A total of 40 students were used as the sample (evenly split between the two groups); the intervention of the experimental group was eight weeks, two sessions a week. Various tools were used such as a test of basic basketball skills such as passing, shooting, dribbling and ball handling and a performance observation form. The statistical analysis of the outcomes was performed with respect to the descriptive statistics (mean, standard deviation) and t -test of related and independent samples. The results showed that there were significant differences in favor of the experiment group in all the basic skills, which showed that cooperative learning methods had potent impacts in boosting the level of students motor performance. The discussion revealed that the method enhanced social interaction, self-confidence, intrinsic motivation, and cooperation, as per the current educational and psychological theories, such as the theory of Vygotsky (1978) and Johnson and Johnson (2019). The article suggests the implementation of the cooperative learning methods in the physical education classes, educating the teachers on how to apply them, and carrying out similar research to analyze their applicability in other team sports.